Association between Zika virus and fetopathy: a prospective cohort study in French Guiana. (4th May 2017) - Pomar, L.; Malinger, G.; Benoist, G.; Carles, G.; Ville, Y.; Rousset, D.; Hcini, N.; Pomar, C.; Jolivet, A.; Lambert, V.
ABSTRACT: Objective: To establish the incidence of fetal central nervous system (CNS) anomalies (including microcephaly), signs of congenital infection and fetal loss in pregnant women infected with Zika virus (ZIKV) and non‐infected pregnant women in western French Guiana. Methods: This prospective cohort study was conducted between 1 January and 15 July 2016. We evaluated and compared clinical and fetal ultrasound examinations of 301 pregnant women with biological confirmation of ZIKV infection and 399 pregnant women who were negative for ZIKV infection. Results: Overall, the total number of fetuses with CNS involvement was higher in the infected than in the control group (9.0% vs 4.3%; relative risk, 2.11 (95% CI, 1.18–4.13)). Anomalies of the corpus callosum and presence of cerebral hyperechogenicities were significantly more common in the infected group. There was an increased risk of microcephaly in the infected compared with the control group (1.7% vs 0.3%; relative risk, 6.63 (95% CI, 0.78–57.83)), although this was not statistically significant. When the mother was infected during the first or second trimester, there was a greater risk of severe CNS involvement, more signs of infection and intrauterine fetal death than with infection in the third trimester. The rate of vertical transmission in the exposed group was 10.9%. Conclusion: ZIKV infection during pregnancy is associated with a significant risk of fetal CNS involvement and intrauterine fetal death, particularly when infection occurs during the first or second trimesters. Microcephaly was not present in every case of congenital ZIKV syndrome that we observed. Until more is known about this disease, it is paramount to evaluate suspected cases by detailed neurosonography on a monthly basis, paying particular attention to the corpus callosum and the presence of hyperechogenic foci. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.